INTEGRASI NILAI-NILAI SIRAH RASULULLAH SAW DALAM INOVASI PENDIDIKAN UNTUK MEMBANGUN KARAKTER GENERASI MASA KINI - Luthfi; Alvionita Simanjuntak, Anni; Marlina, Lilis (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This study examines the integration of values from the Sirah of the Prophet Muhammad (PBUH) as a foundation for educational innovation to build the character of today's generation. The main focus is analyzing the moral, ethical, and spiritual values contained in the Sirah Nabawiyah, such as honesty, compassion, and leadership, and their application in technology-based modern education. The research employs a qualitative approach with literature study, involving analysis of primary sources like the Qur'an and Hadith, as well as secondary sources including works of classical and contemporary scholars. Data analysis techniques include identification, classification, and interpretation of key themes. The results indicate that integrating the values of Sirah Nabawiyah into education can strengthen students' character through innovative approaches such as e-learning, gamification, and project-based learning. This implementation is relevant to addressing the challenges of the digital era, including moral degradation and weak social ethics. In conclusion, integrating Sirah values into the educational curriculum not only develops a generation with noble character but also enhances competitiveness in facing global challenges.